KETERLIBATAN AYAH DAN KECENDERUNGAN MENJADI KORBAN KEKERASAN DALAM KONFLIK BERPACARAN REMAJA PEREMPUAN - ANNA ARMEINI RANGKUTI; ADJENG HAYU HERNINGTYAS (Journal of Research and Measurement in Psychology, 2016)
The study is done to know the influence of father involvement on the tendency to become victims of conflict in dating relationship. Researcher used scale quantitative methods psychology. Researcher used adapted instrument, namely Nurturant Fathering Scales & Father Involvement Scale subscale Reported Father Involvement Scale and Conflict in Adolescent Dating Relationship Inventory (CADRI). There are 350 samples of respondent which is adolescent girl who has romantic relationship and living with their father. The data processing used in the testing of hypotheses analytics regression. The result of the influence is negative, this means that the higher father involvement, the lower on the tendency to become victims of dating violence in adolescent girl. The big influence of produced father involvement on the tendency to become victims of dating violence is 2,4% and the rest influenced by other factors.